2014
DOI: 10.1088/0031-9155/59/19/5921
|View full text |Cite
|
Sign up to set email alerts
|

The use of tetrahedral mesh geometries in Monte Carlo simulation of applicator based brachytherapy dose distributions

Abstract: Accounting for brachytherapy applicator attenuation is part of the recommendations from the recent report of AAPM Task Group 186. To do so, model based dose calculation algorithms require accurate modelling of the applicator geometry. This can be non-trivial in the case of irregularly shaped applicators such as the Fletcher Williamson gynaecological applicator or balloon applicators with possibly irregular shapes employed in accelerated partial breast irradiation (APBI) performed using electronic brachytherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The finite element model involved one contact pair including the outer surface of the roll and the top surface of the workpiece, which was defined as surface-to-surface contact utilising finite sliding formulation and surface-to-surface discretisation method, and modelled with frictional interface adopting a friction coefficient of 0.15 [74]. The outer surface of the roll in the contact pair was set as master surface, in view of higher stiffness and consequently less deformation of the roll [75], which was meshed with linear brick elements (C3D8R) with an element size of 0.3 mm, whilst the top surface of the workpiece was selected as the corresponding slave surface with the whole workpiece meshed with 10-node modified quadratic tetrahedron elements (C3D10M), with a relatively small element size of 0.125 mm, for the sake of precise description of the complex geometry of grain boundaries as well as non-penetration of the nodes at the outer surface of the roll [76,77].…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…The finite element model involved one contact pair including the outer surface of the roll and the top surface of the workpiece, which was defined as surface-to-surface contact utilising finite sliding formulation and surface-to-surface discretisation method, and modelled with frictional interface adopting a friction coefficient of 0.15 [74]. The outer surface of the roll in the contact pair was set as master surface, in view of higher stiffness and consequently less deformation of the roll [75], which was meshed with linear brick elements (C3D8R) with an element size of 0.3 mm, whilst the top surface of the workpiece was selected as the corresponding slave surface with the whole workpiece meshed with 10-node modified quadratic tetrahedron elements (C3D10M), with a relatively small element size of 0.125 mm, for the sake of precise description of the complex geometry of grain boundaries as well as non-penetration of the nodes at the outer surface of the roll [76,77].…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…Also, the direct implementation of mesh-based system designs in GATE is not straight-forward and requires multiple tedious steps. Initial reports indicated that simulation of complex mesh-based models might not be practical due to the time necessary to navigate through many triangles linearly scales with their number (Kim et al 2011, Poole et al 2012, Fonseca et al 2014. Nevertheless, more recent developments in Geant4 upon which GATE is built, have considerably improved the navigation through triangulated mesh objects enabling the simulation of more complex meshes in an efficient manner (Asai et al 2015, Allison et al 2016.…”
Section: Introductionmentioning
confidence: 99%